BLU Financial Ratio Analysis for Performance Measurement - Cucu Nurhayati; Indra Cahya Kusuma; Didi; Surahmat (Institut Bisnis dan Informatika Kesatuan, 2024)
This research aims to determine the BLU Financial Ratio Analysis for Performance Measurement at Dr. Lung Hospital. M. Goenawan Partowidigdo Cisarua Bogor Based on Director General of Treasury Regulation No.36/PB/2016 for the 2019-2023 Period. This research uses quantitative descriptive research with data collection methods, namely field research, interviews, observation, documentation and literature review. Financial ratio analysis is carried out using liquidity, solvency, activity and profitability ratios, with 7 ratio indicators - financial ratios and BLU management compliance aspects used in research on measuring hospital financial performance, including cash ratio, current ratio, receivables collection period, turnover. fixed assets, compensation for fixed assets, equity compensation and PNBP income against operational costs. The results of the research show that the analysis of financial performance at RSPG Cisarua Bogor based on analysis of liquidity, solvency, activity and profitability ratios shows good performance and based on financial performance indicators of the hospital, the financial performance of RSPG Cisarua Bogor from 2019-2023 is included in the predicate of both A and AA.